2018
DOI: 10.1021/acs.energyfuels.8b02085
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Characterization of Petroleum Acids by Distillation, Solid Phase Extraction Separation, and Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: Crude acids or petroleum acids are considered to be one of the prime contributors to corrosion, emulsion, and fouling issues across upstream, downstream, and chemical operations. Thus, the composition of crude acids has been extensively studied in the last several decades. To achieve molecular level characterization, mass spectrometry is typically applied. However, one of the challenges in mass spectrometry characterization is that the dynamic range of the technique can severely limit the compositions observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Broadband FT-ICR MS is uniquely suited for molecular-level characterization of ultra-complex mixtures because it can resolve and identify tens of thousands of elemental compositions in a single analysis in a matter of minutes, irrespective of the boiling point. When combined with separations, FT-ICR MS constitutes a powerful tool to assess petroleum molecular composition and understand the compositional trends responsible for petroleum phase behavior, fouling, and refining. , …”
Section: Resultsmentioning
confidence: 99%
“…Broadband FT-ICR MS is uniquely suited for molecular-level characterization of ultra-complex mixtures because it can resolve and identify tens of thousands of elemental compositions in a single analysis in a matter of minutes, irrespective of the boiling point. When combined with separations, FT-ICR MS constitutes a powerful tool to assess petroleum molecular composition and understand the compositional trends responsible for petroleum phase behavior, fouling, and refining. , …”
Section: Resultsmentioning
confidence: 99%
“…The high molecular weight species will not be detected if the sample is analyzed "as is" due to dynamic range limitations as shown in Figure 2. 48 Clingenpeel et al 49 further combined physical distillation and MAPS to determine full acid composition for whole crude oils. The work demonstrated that a single FT-ICR measurement only provides a fingerprint of the petroleum acids.…”
Section: ■ Separation Approachesmentioning
confidence: 99%
“…(−) MALDI allowed the detection of highly oxidized O x species ( x = 1–9, 11) that were not observed in the (−) ESI mass spectra. More recently, Clingenpeel et al utilized multiple separation methods followed by analysis using (−) ESI 15 T FTICR MS to increase the dynamic range of the analysis of NAs in crude oil . The crude oil was first distilled into fractions that included vacuum gas oil (VGO) and vacuum residue (VR).…”
Section: Applicationsmentioning
confidence: 99%
“…More recently, Clingenpeel et al utilized multiple separation methods followed by analysis using (−) ESI 15 T FTICR MS to increase the dynamic range of the analysis of NAs in crude oil. 125 The crude oil was first distilled into fractions that included vacuum gas oil (VGO) and vacuum residue (VR). The NAs were then isolated from VGO, VR, and the original crude oil by using SPE and fractionated based on their MW by using the SPE method discussed above, followed by analysis using (−) ESI 15 T FTICR MS. Mass spectra measured for the VGO and VR fractions revealed small acidic compounds with two to four oxygens that were not detected in the original crude oil.…”
Section: Sophisticated Instrumentation Requiredmentioning
confidence: 99%